Evaluation of macular structure and thickness using spectral optical coherence tomography SOCT Spectralis in children after prior laser photocoagulation performed due to the retinopathy of prematurity - Chrzanowska-Grenda, Beata; Oziębło-Kupczyk, Monika; Szumiński, Michał; Grenda, Marek; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Objectives : To evaluate morphobiometric properties of the macula (its structure and thickness) in children with a known history of retinopathy of prematurity using optical coherence tomography (SLO/OCT Spectralis). Material and methods : 16 subjects (group B1) (mean age 9.2 years) with a history of stage 3 retinopathy of prematurity treated with retinal laser photocoagulation and 18 subjects (group B2) with a history of spontaneously regressing retinopathy of prematurity (mean age 10.2 years) were studied prospectively. The control group consisted of 21 healthy subjects (group K) (mean age 10.9 years). Each participant underwent a thorough ocular examination and had an optical coherence tomography performed. The U Mann-Whitney and Spearman’s rank correlation tests were used for statistical analyses. Results : The minimum central foveal thickness and total macular volume were significantly higher in both study groups (B1 and B2) as compared to the control group (K). The subfoveal choroidal thickness was reduced in both study groups (B1 and B2), as compared to the control group (K). Conclusions : The altered macular structure in eyes with the history of retinopathy of prematurity is related to the presence of all retinal layers within the fovea. However, these changes do not significantly affect visual acuity.